PERLINDUNGAN TERHADAP PEMEGANG HAK CIPTA FILM KELUARGA CEMARA BERDASARKAN UNDANG-UNDANG HAK CIPTA - Dani Ikhwanto; Rakhmita Desmayanti (Fakultas Hukum Universitas Trisakti, 2021)
In the protection of copyright infringement on internet-based means of copyright law in article 54 has set it. One of them is the supervision of the dissemination of copyrighted works. Law enforcement measures that can be taken by copyright holders to protect their work is mediation, based on the provisions of Article 95 Paragraph 4 UUHC to conduct criminal prosecution must first take dispute resolution through mediation. After that new copyright holders can sue criminally. The research was conducted with normative legal research methods using secondary data. Based on article 120 of the UUHC this criminal offense is a complaint offense. Article 105 of the Copyright Act also mentions the right to file a civil suit does not reduce the creator's right to sue criminally. If the copyright holder filed a lawsuit for compensation then according to Article 99 UUHC the lawsuit for compensation is submitted to the commercial court. The last step that can be taken by copyright holders is a report on the closure of content carried out to the Government in this case the Director General of IPR in collaboration with the Director General of APTIKA in accordance with the order of UUHC Article 56 Paragraph (2).